Money and Credit Under Currency Substitution - Rodriguez, Carlos (IMF Working Papers; Working Paper ;, 1992)
This paper examines the effects on the supply of money and credit of a repatriation of foreign assets in an economy subject to currency substitution. In the absence of 100 percent reserve requirements, such a change in the location of deposits, which is not compensated by an increase in money demand, induces a credit boom that works itself out through a transitory current account deficit and real currency appreciation. These results are illustrated with data from the recent experience in Argentina and Peru where local banks have been authorized to capture dollar deposits from residents.